Pulsar revival in neutron star mergers: multimessenger prospects for the discovery of pre-merger coherent radio emission. Issue 3 (12th December 2022) - Cooper, A J; Gupta, O; Wadiasingh, Z; Wijers, R A M J; Boersma, O M; Andreoni, I; Rowlinson, A; Gourdji, K
ABSTRACT: We investigate pre-merger coherent radio emission from neutron star mergers arising due to the magnetospheric interaction between compact objects. We consider two plausible radiation mechanisms, and show that if one neutron star has a surface magnetic field B s ≥ 10 12 G, coherent millisecond radio bursts with characteristic temporal morphology and inclination angle dependence are observable to Gpc distances with next-generation radio facilities. We explore multi-messenger and multi-wavelength methods of identification of a neutron star merger origin of radio bursts, such as in fast radio burst surveys, triggered observations of gamma-ray bursts and gravitational wave events, and optical/radio follow-up of fast radio bursts in search of kilonova and radio afterglow emission. We present our findings for current and future observing facilities, and make recommendations for verifying or constraining the model.